Pemanfaatan Website E-Learning Terhadap Minat Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan - Hesti Puspita Sari; Ria Yuni Lestari; Febrian Alwan Bahrudin (CV. ULIL ALBAB CORP, 2025)
This research was based on the results of direct field observations conducted at SMK Pasundan 1 Serang City. The results of this investigation were derived from direct field observations conducted at SMK Pasundan 1 Serang City. This research indicated that the conventional learning previously implemented at SMK Pasundan 1 Serang City was insufficient to draw students' interest in learning. The approach lacked innovation and creativity. As a result, the lessons become tedious and repetitive. The objective of this study was to investigate the extent to which students' interest in the learning process of Pancasila and Civics Education subjects is influenced by the use of E-learning websites. The descriptive qualitative research methods used in this study were utilized to provide a detailed account of the conditions of E-learning website utilization and its influence on the learning interest of class XII students at SMK Pasundan 1 Serang City. The results indicated that the implementation of E-learning websites in learning Pancasila and Citizenship Education has been successful, as evidenced by the utilization of these websites in the learning process and the schools' policies. Using an E-learning website in the classroom as a learning media includes various features, such as student attendance, material delivery, and individual or group questions for evaluation, which can also be used as an exam media. Thus, e-learning websites are essential to students' interest in learning during the learning process and following technological developments in education.